(untitled) (Asian Journal of Medical and Biological Research, 2025)
Epigenetic changes are increasingly acknowledged as crucial factors in the beginning of both blood cancers and solid tumors. These amendments, such as DNA methylation and histone changes, influence gene expression and cellular activities without altering the fundamental DNA sequence. This review aims to provide a comprehensive analysis of the role of DNA methylation and histone modifications in cancer pathogenesis, with a focus on their potential applications as diagnostic, prognostic, and therapeutic biomarkers. The review synthesizes findings from recent studies on epigenetic alterations in cancer, emphasizing their mechanistic roles in tumorigenesis, therapeutic resistance, and tumor heterogeneity. Relevant studies were chosen for their focus on DNA methylation, histone modifications, and their clinical significance. This review highlights the frequent occurrence of tumor suppressor gene hypermethylation and oncogene hypomethylation across various cancers. Additionally, changes in histone modifications, such as acetylation, methylation, and phosphorylation, can alter chromatin configuration and play a significant role in the emergence of oncogenic characteristics. The crosstalk between these epigenetic mechanisms contributes to the reprogramming of the cancer epigenome, driving tumor heterogeneity and resistance to therapy. Understanding the mechanisms of epigenetic alterations in cancer provides new opportunities for developing targeted therapies and improving patient outcomes. Epigenetic biomarkers hold promise for early diagnosis, prognosis, and personalized treatment strategies. This review underscores the importance of epigenetic research in oncology, offering insights into novel therapeutic targets and strategies. It also highlights the need for further studies to translate these findings into clinical applications, ultimately reshaping cancer treatment paradigms. Asian J. Med. Biol. Res. 2025, 11(2), 23-36